Feasibility, Safety, and Clinical Performance of Self-apposing Stents for Left Main Stenosis - Krzysztof Pujdak; Jan Kähler; Marc Werner (US Cardiology Review)
Drug-eluting stents (DES) are the gold standard for percutaneous coronary interventions (PCI); however, technical and anatomical challenges need to be addressed to ensure optimal apposition and prevent late adverse events. Complex vessel anatomies, including ectatic or aneurysmatic vessels, or significant differences in diameter in left main stenosis of the coronary artery, are clinical indications in which current PCI techniques attempt to shape conventional DES to follow vessel anatomy, thus modifying the original stent scaffold and its properties. However, due to their design, balloon-expandable cobalt–chromium and cobalt–nickel DES have limitations regarding their expansion capacity, which can result in undersizing and malapposition. New stent scaffolds have recently been introduced into clinical practice to address these challenging anatomies, including a drug-eluting nitinol stent platform. The nature of the nitinol device allows conformability to the native vessel, covering complex anatomies without manual adaptation. In this article, the authors present the rationale and current data on self-apposing nitinol DES in left main stenosis, and suggest that the device may be safely and effectively used with comparable rates of adverse cardiovascular events, as seen with second-generation balloon-expandable DES.